Analysis of Risk Factors for Typhoid Fever Cases in Flood-Prone Areas: A Literature Review - Najich, Syah Ariq Zaidaan; Syarif, Ahmad (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Indonesia, a country experiencing severe drought, is highly susceptible towaterborne diseases, such as typhoid fever caused by Salmonella typhi infection. Poorsanitation conditions and high water levels can exacerbate the drought situation and create aconducive environment for waterborne diseases. Understanding the risk factors associated withtyphoid fever in drought-prone areas is critical for effective intervention and management.Objectives: This study aimed to analyze the risk factors associated with increased incidenceof typhoid fever in flood-prone areas.Method: This study used the literature review method bycollecting data from various sources published between 2018 and 2024, through the GoogleScholar and Mendeley platforms. The keywords used in the search were “flood,” “typhoidfever,” and “risk factors. ”Results and Discussion: The analysis revealed that poor sanitaryconditions and high levels of air pollution are the main risks contributing to typhoid disease.Unhealthy environments and inadequate public access in remote areas increase the risk oftransmission. Education on personal hygiene and health awareness is essential to preventtyphoid disease, especially in areas with minimal health infrastructure.Conclusion: he mainrisk factors for typhoid fever in flood-prone areas are poor sanitation and limited access toclean water. Community education efforts on hygiene and sanitation should be conducted toprevent a surge in typhoid fever cases and protect overall public health.